2015
DOI: 10.1108/jsm-03-2014-0081
|View full text |Cite
|
Sign up to set email alerts
|

Foreign or domestic: who provides better customer service?

Abstract: Purpose – The purpose of this paper is to investigate the role of customer service employees’ (CSEs) competence and service recovery outcomes on service evaluations of foreign and domestic CSEs. Design/methodology/approach – Three experiments were conducted to test and validate the proposed hypotheses. The participants were told a cover story that they were either listening to (Study 2) or reading (Studies 1 and 3) a real conversation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Are the same benefits expected from both types of banks? Poddar et al (2015) show that FB employees, in general, are more favorably viewed by customers. This gives FBs more elbow room to deal with customer dissatisfaction.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Are the same benefits expected from both types of banks? Poddar et al (2015) show that FB employees, in general, are more favorably viewed by customers. This gives FBs more elbow room to deal with customer dissatisfaction.…”
Section: Literature Reviewmentioning
confidence: 91%
“…The fourth category, a different approach to address stereotypes, recommends focussing on delivering high-quality services and ignoring potential stereotypical perceptions because excellent service delivery can render stereotypes irrelevant. For example, in a cultural context, the country-of-origin of a service employee was not as important as the competence of the employee (Poddar et al 2015). In a gender context, the most important determinant of customer evaluations was the service outcome, not stereotypical perceptions (Mohr and Henson 1996;Pinar et al 2017).…”
Section: Managerial Implications In Existing Literaturementioning
confidence: 98%
“…Studies have shown that in a positive service experience, stereotypical characteristics do not seem to be influential. In contrast, after a negative service outcome, customers evaluate minority service providers more poorly than traditional ones (Poddar et al 2015;Wang et al 2013). Interestingly, in a gender context, Matta and Folks (2005) found that due to lower expectations in the beginning, initially negatively stereotyped service providers who deliver an excellent service outcome are evaluated even higher than standard service employees delivering the same service outcome.…”
Section: Context Factorsmentioning
confidence: 99%
See 2 more Smart Citations